2021
DOI: 10.1093/neuonc/noab180.033
|View full text |Cite
|
Sign up to set email alerts
|

OS07.5A Diagnostic Instrument for Mild Aphasia (DIMA): sensitive and valuable addition to standard language assessment in glioma patients

Abstract: BACKGROUND Low-grade glioma (LGG) patients typically suffer from mild aphasia that often cannot be detected with standard aphasia tests. The Diagnostic Instrument for Mild Aphasia (DIMA) is the first standardized test-battery to assess mild language disorders. We investigate pre- and postoperative linguistic abilities of LGG and high-grade glioma (HGG) patients with the DIMA. METHODS The DIMA consists of subtests that tap pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Second, tumor in the right hemisphere was more often observed in the musical group which could be a confounding on language performance, considering that language is often lateralized in the left hemisphere. However, we argue that this does not influence our results as prior research found that hemispheric lateralization does not affect language performance on the DIMA scale in glioma patients ( Mooijman et al, 2021 ; Satoer et al, 2022 ).…”
Section: Discussionmentioning
confidence: 46%
“…Second, tumor in the right hemisphere was more often observed in the musical group which could be a confounding on language performance, considering that language is often lateralized in the left hemisphere. However, we argue that this does not influence our results as prior research found that hemispheric lateralization does not affect language performance on the DIMA scale in glioma patients ( Mooijman et al, 2021 ; Satoer et al, 2022 ).…”
Section: Discussionmentioning
confidence: 46%
“…They suggest this right involvement may implicate the use of a strategy for mental imagery. Another study on language testing in glioma patients using the Diagnostic Instrument for Mild Aphasia (DIMA, Satoer et al., 2022), which includes subtests under time pressure, also showed impairments in left‐hemispheric and right‐hemispheric glioma patients (Mooijman et al., 2021). This suggests that some language tests with time pressure such as subtests from DIMA or category fluency are sensitive in all glioma patients independent of hemispheric tumour location.…”
Section: Discussionmentioning
confidence: 99%